Two-tier and negotiated tender offers: The imprisonment of the free-riding shareholder - Comment, Robert; Jarrell, Gregg A. (Journal of Financial Economics, 1987)
We measure the differential effects on shareholder wealth and tendering behavior of any-or-all, two-tier and partial tender offers and find no evidence that shareholders are disadvantaged by front-end-loaded corporate takeovers. Shareholders fare as well when the terms of an offer for control are negotiated with target-firm management as when they are not. Most cash tender offers executed between 1981 and 1984 were negotiated, and almost all two-tier offers were negotiated.